Polypharmacy and Medication-Related Problems in Hemodialysis Patients: A Call for Deprescribing - Majed Alshamrani; Abdullah Almalki; Mohamed Qureshi; Oyindamola Yusuf; Sherine Ismail (Pharmacy, 2018)
Polypharmacy is a common problem among hemodialysis patients. It is associated with increased hospital admissions, morbidity, mortality, Medication-Related Problems (MRPs), and expenditures. There is a paucity of data on the prevalence of polypharmacy in our setting. This study aims to determine the prevalence of polypharmacy and MRPs and to assess its predictors. We conducted a cross-sectional study in the outpatient hemodialysis unit. A pharmacy resident assessed electronic prescribing records to identify MRPs and discussed therapeutic interventions to enhance effective therapeutic regimens over a three months period. Eighty-three patients were included. The median age was 63 (Interquartile range; IQR = 22), 50% were males, and the mean number of co-morbidities was 3.14 ± 1.64. The prevalence of polypharmacy was 97.6% with a 95% CI (91.6%–99.7%). Medication use without indication, was the highest identified MRPs at 36% (102/280), followed by subtherapeutic dosing at 23% (65/280), and overdosing at 15% (41/280). The number of comorbidities, the presence of ischemic heart disease, and respiratory diseases were the main predictors of the increased number of medications. Polypharmacy is highly prevalent among the Saudi hemodialysis population. A review of the medications prescribed by the pharmacist facilitated the identification of MRPs and provided opportunities for deprescribing to optimize medication use and to reduce polypharmacy in hemodialysis patients.